1993
DOI: 10.1007/bf01309840
|View full text |Cite
|
Sign up to set email alerts
|

Role of Langerhans cells and other dendritic cells in viral diseases

Abstract: Langerhans cells are part of a vast system of potent antigen-presenting cells known under the name of dendritic cells. During the last decade, much has been learned on dendritic cell involvement in the immune response to infectious diseases. This review briefly summarizes our current understanding of the role played by Langerhans cells and other dendritic cells in the pathogenesis of DNA and RNA virus infections. These data may form the basis for the development of innovative approaches in the diagnosis, preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 145 publications
0
26
0
Order By: Relevance
“…Recent evidence implicates dendritic cells in certain pathological processes, especially autoimmune diseases such as multiple sclerosis, juvenile diabetes and psoriasis; an increased number of dendritic cells have been found in the synovial fluid of patients with rheumatoid arteritis (KING and KATZ, 1990;KAMPER-DIJK et al, 1993;SPRECHER and BECKER, 1993). Animal experiments have additionnally shown that dendritic cells are a target for effector lymphocyte responsers with resulting inhibition of the T-cell activity pathway (KING and KATz, 1990;KAMPERDIJK et al, 1993).…”
Section: Identification Of Dendtitic Cells In the Arterial Intimamentioning
confidence: 99%
“…Recent evidence implicates dendritic cells in certain pathological processes, especially autoimmune diseases such as multiple sclerosis, juvenile diabetes and psoriasis; an increased number of dendritic cells have been found in the synovial fluid of patients with rheumatoid arteritis (KING and KATZ, 1990;KAMPER-DIJK et al, 1993;SPRECHER and BECKER, 1993). Animal experiments have additionnally shown that dendritic cells are a target for effector lymphocyte responsers with resulting inhibition of the T-cell activity pathway (KING and KATz, 1990;KAMPERDIJK et al, 1993).…”
Section: Identification Of Dendtitic Cells In the Arterial Intimamentioning
confidence: 99%
“…Dendritic cells are thought to play an important role in presenting antigen to naive T cells during viral infection (Austyn, 1998;Sprecher and Becker, 1993;Steinman, 1991;Steinman et al, 1993), and these cells are located in the portal area (Kudo et al, 1997;Prickett et al, 1988). The host immunoreaction to HCV-infected cells may therefore be initiated in the portal and periportal areas.…”
mentioning
confidence: 99%
“…LCs play an important role in the immune responses to cutaneous infections caused by Herpes simplex virus types 1 and 2, poxvirus, papillomavirus, varicella virus, and other pathogens that cause skin infections [23]. LCs may contribute to the anti-infection immunity by at least two mechanisms, induction of cellular and humoral immunities by presenting antigen of the infectious agents to the immune system and secretion of cytokines that have direct antiviral activities [24].…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Vice versa, activation of LCs locally or systemically correlates with the resistance to infection with these viruses [26]. LCs not only contribute to the control of primary infections, but also play a role in the control of recurrent viral infections caused by HSV-1 [23].…”
Section: Infectious Diseasesmentioning
confidence: 99%